2014
DOI: 10.1186/1477-7827-12-31
|View full text |Cite
|
Sign up to set email alerts
|

Delaying the oocyte maturation trigger by one day leads to a higher metaphase II oocyte yield in IVF/ICSI: a randomised controlled trial

Abstract: BackgroundThe negative impact of rising progesterone levels on pregnancy rates is well known, but data on mature oocyte yield are conflicting. We examined whether delaying the oocyte maturation trigger in IVF/ICSI affected the number of mature oocytes and investigated the potential influence of serum progesterone levels in this process.MethodsBetween January 31, 2011, and December 31, 2011, 262 consecutive patients were monitored using ultrasound plus hormonal evaluation. Those with > =3 follicles with a mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…Vandekerckhove et al showed that in patients with low serum progesterone level (≤1 ng/ml) 24 hr delaying in the oocyte maturation trigger could cause to more total oocytes and mainly more mature oocytes (MII) in contrast with those triggered on the same day. Although, no meaningful differences were seen in the pregnancy rates and pregnancy outcomes between two groups ( 10 ). But in the patients with higher serum progesterone level (>1 ng/ml) delaying the oocyte maturation trigger by 24 hr accompanied with no difference in IVF cycle characteristics ( 10 ).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Vandekerckhove et al showed that in patients with low serum progesterone level (≤1 ng/ml) 24 hr delaying in the oocyte maturation trigger could cause to more total oocytes and mainly more mature oocytes (MII) in contrast with those triggered on the same day. Although, no meaningful differences were seen in the pregnancy rates and pregnancy outcomes between two groups ( 10 ). But in the patients with higher serum progesterone level (>1 ng/ml) delaying the oocyte maturation trigger by 24 hr accompanied with no difference in IVF cycle characteristics ( 10 ).…”
Section: Introductionmentioning
confidence: 84%
“…Elevated serum progesterone levels on the day of HCG administration (p>1.5 ng/ml) decreased ongoing pregnancy and delivery rates ( 7 , 9 ). Vandekerckhove et al showed, if the progesterone level is higher than 1 ng/ml, delaying the administration of HCG by 24 hr has no effect on the number of mature oocytes ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The course of stimulation was check by ultrasound monitoring. As soon as 50% of the follicles were >10-18 mm in diameter, oocyte maturation and retrieval was performed according to Vandekerckhove et al (13).…”
Section: Oocyte Retrieval and Blastocyst Biopsymentioning
confidence: 99%
“…Ultrasound monitoring was done to check the course of stimulation. As soon as 50% of the follicles >10 mm reached a diameter of R18 mm, oocyte maturation and retrieval was performed according to Vandekerckhove et al (47).…”
Section: Ovarian Hyperstimulation Protocolmentioning
confidence: 99%